2019
DOI: 10.1021/acs.jafc.8b06893
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Aptasensor Based on Truncated Aptamer and Trivalent DNAzyme for Vibrio parahemolyticus Determination

Abstract: In this work, after optimizing the original aptamer sequence by truncation and site-directed mutagenesis, a simple and sensitive colorimetric aptasensor was established for detecting the widespread food-borne pathogen Vibrio parahemolyticus (V. parahemolyticus). The detection strategy was based on the competition for an V. parahemolyticus specific aptamer between its complementary DNA (cDNA) and V. parahemolyticus. The aptamer-conjugated magnetic nanoparticles (MNPs) were used as capture probes, and the G-quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 38 publications
0
39
0
1
Order By: Relevance
“…All these demonstrated that CLICK-T has higher catalytic effects towards Cu(II)AAC than CLICK-17. The reasons maybe due to that CLICK-T has shorter length and could be easier to contact and combine with the analyte [25].…”
Section: The Feasibility Of Copper Detection By the Click-t Modified ...mentioning
confidence: 99%
“…All these demonstrated that CLICK-T has higher catalytic effects towards Cu(II)AAC than CLICK-17. The reasons maybe due to that CLICK-T has shorter length and could be easier to contact and combine with the analyte [25].…”
Section: The Feasibility Of Copper Detection By the Click-t Modified ...mentioning
confidence: 99%
“…Under optimal reaction conditions, a considerable linear detection range of 10 2 to 10 7 CFU/mL was observed, in addition to a low detection limit of 10 CFU/mL. Therefore, the synthesized biosensor showed good sensitivity and accuracy, making it a viable alternative for monitoring food quality without the need for more complicated operations [382].…”
Section: Food Applicationsmentioning
confidence: 94%
“…Sun et al [ 119 ] have reported a colorimetric aptasensor for detecting V. parahaemolyticus comprised of three parts: magnetic NPs (MNPs) modified with streptavidin, a biotinylated V. parahemolyticus aptamer, and a label-free ssDNA that is complementary (cDNA) to the aptamer and has a G-quadruples component. The aptamer was conjugated to MNPs via the biotin−streptavidin interaction, and then the cDNA was partly hybridized with aptamer thus allowing ssDNA to attach to the surface of the MNPs.…”
Section: Food and Water Analysismentioning
confidence: 99%